Estimativa das frequências alélicas dos15 marcadores autossômicos STR CODIS da população goianiense do Brasil Central - Ferreira, Lindomar Valentim (2011)
The population genetics aims to study the allelic and genotypic frequencies in populations and the mechanisms that these frequencies change over generations. This study aims to estimate and compare the allele frequencies of 15 autosomal STR markers, sheets of 501 tests the genetic link in 986 individuals in the population of Goiânia-Goiás. The markers that showed higher numbers of alleles were D18S51 and Penta E with 20 to 19. The marker that had allele frequency was higher for the TPOX 8 allele. Other statistical parameters analyzed demonstrated high PIC, PD and PE for the marker Penta E. Analysis of allele frequencies obtained in this study were statistically compared with populations of five regions of Brazil, by Student's t test, not intra-population differences were observed (p> 0.05). In this context, the genetic database based on the values of the allele frequencies of the population of Goiânia, can be used in testing the genetic link, as well as in studies of human identification, due to the similarities observed in other Brazilian populations.